The mediating role of subjective well-being in the relationship between ethical leadership behaviors of school principals and organizational cynicism according to teacher perceptions - GÜLER, Hüseyin; Ayık, Ahmet (Edelweiss Applied Science and Technology, 2025)
This study examined the mediating role of subjective well-being in the relationship between school principals ‘ethical leadership behaviours and organisational cynicism according to teachers’ perceptions. Relational survey model, one of the quantitative research methods, was used in the study. The population of the study consisted of teachers working in primary and secondary schools in Tuşba district of Van province of Turkey in 2022-2023 academic year. The sample group of the study consisted of 430 volunteer teachers determined by ‘stratified sampling’ method, which is one of the non-probability sampling methods. Ethical Leadership Scale, Organisational Cynicism Scale and Teacher Subjective Well-Being Scale were used as data collection tools. The data were analysed using Statistical Package for the Social Sciences (SPSS) and Analysis of Moment Structures (AMOS) statistical programs. As a result of the research, a moderate negative significant relationship was found between school principals ‘ethical leadership behaviours and teachers’ organisational cynicism levels, and a moderate negative significant relationship was found between teachers' organisational cynicism levels and their subjective well-being. In addition, it was determined that there was a significant positive relationship between school principals ‘ethical leadership behaviours and teachers’ subjective well-being. Finally, it was concluded that subjective well-being has a partial mediating role in the relationship between ethical leadership and organisational cynicism. It was concluded that ethical leadership behaviours exhibited by school principals affect teachers' organisational cynicism levels both directly and indirectly through subjective well-being.